1996
DOI: 10.1016/0378-4266(95)00003-8
|View full text |Cite
|
Sign up to set email alerts
|

A note on price-volume dynamics in an emerging stock market

Abstract: We present a continuum economy with risk neutral agents having heterogeneous expectations and restricted short sales. A stochastic version of the model is also formulated and the resulting time series behavior of the price and volume series under a specific money supply process derived. The implications of the model are tested in the emerging Turkish stock market where institutional arrangements comply with the restrictions of the model. The results indicate that, as predicted by the model, price levels and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 9 publications
1
18
1
Order By: Relevance
“…This conclusion was found in Latin America stock markets as reported by Saatccioglu and Starks 8 and Christofi and Pericli, 41 in the Swedish stock market as reported by Säfvenblad,10 in the New York stock exchange as reported by Gallant et al, 13 in the Taiwan stock market as reported by Hsin et al, 15 in selected developed stock markets as reported by Sabri,18 in selected emerging stock markets as reported by Sabri 17 and De Santis and Imrohorglu, 42 in the Shanghai stock exchange as reported by Song et al 16 and Mei et al, 12 and in the Turkish stock market as reported by Basci et al 43 The question arises here as to the major factors that may drive the Arab stock market to volume volatility. In general, the trading volatility may be associated to the transmission impact from other major markets and to the volatility spillovers concept from leading stock markets.…”
Section: Discussionmentioning
confidence: 91%
“…This conclusion was found in Latin America stock markets as reported by Saatccioglu and Starks 8 and Christofi and Pericli, 41 in the Swedish stock market as reported by Säfvenblad,10 in the New York stock exchange as reported by Gallant et al, 13 in the Taiwan stock market as reported by Hsin et al, 15 in selected developed stock markets as reported by Sabri,18 in selected emerging stock markets as reported by Sabri 17 and De Santis and Imrohorglu, 42 in the Shanghai stock exchange as reported by Song et al 16 and Mei et al, 12 and in the Turkish stock market as reported by Basci et al 43 The question arises here as to the major factors that may drive the Arab stock market to volume volatility. In general, the trading volatility may be associated to the transmission impact from other major markets and to the volatility spillovers concept from leading stock markets.…”
Section: Discussionmentioning
confidence: 91%
“…Basci, Ozyildinm, and Aygodan (1996) develop a stochastic model with restrictions on short sales and risk neutral agents having heterogeneous expectations. Data collected from the Istanbul Securities Exchange during their sample period from January 1988 to March 1991 fit their model's institutional characteristics well.…”
Section: Prior Research and Testable Implicationsmentioning
confidence: 99%
“…The relatively small number of studies which have examined this issue for emerging markets have focused on weekly or monthly data (see Moosa and Al-Loughani 1995, Saacioglu and Starks 1998, Basci et al 1996, Gündüz and Hatemi-J 2005. In contrast, our study uses daily data because the short horizon data are more suitable to test causal and dynamic relationships between return, volatility and trading volume.…”
mentioning
confidence: 94%